Gender-linked Differences in the Toys, Television Shows, Computer Games, and Outdoor Activities of 5- to 13-year-old Children. - Cherney, Isabelle D.; London, Kamala (Sex Roles, 2006)
This study was designed to compare how 5- to 13-year-old children's leisure activity preferences differ with age and gender. Responses from 60 boys and 60 girls about their favorite toys, television shows, computer games, and outdoor activities were compared across leisure categories. The results showed that gender was a significant factor. Overall, boys spent more time in these leisure activities than girls did. They spent the most time engaged in sports, watching television, and playing computer games, whereas girls spent the most time watching television. Results from a gender index for all activities indicated that boys' leisure preferences became slightly more masculine with age. For girls, preferences for television shows became more feminine with age, but preferences for toys, computer games, and sports became less feminine. These self-chosen preferences may provide differential opportunities for the development of visual-spatial skills, achievement, initiative, self-regulation, and social skills. Reprinted by permission of the publisher.